(untitled) - Daniels, B. J. (Toronto, Ontario, Canada, 2022)
With the 125th anniversary of Buckhorn, Montana, on the horizon, its the job of straitlaced marshal Leroy Baggins to keep the peace during the four-day celebration. But his focus is distracted when private security owner TJ Walker arrives to help with the event. Shes clearly someone who doesnt play by the rules, a loose cannon who pushes him outside his comfort zone.
Keywords: Police; Fiction; Man-woman relationships; Fiction; Montana; Fiction; Romance fiction; Western fiction